2021
DOI: 10.21577/0103-5053.20210021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preparation Additives on the Antimicrobial Activity and Cytotoxicity of Polypyrrole

Abstract: The search for new biomaterials has increased continuously in recent years and, in this context, the application of polypyrrole (PPy) as a promising material for this function has been reported as a result of positive responses, such as bioactivity and biocompatibility. In this study, PPy was obtained through modifications/adaptations made in methodologies of previous papers, which focused mainly on conductive properties. The use of additives in the synthesis significantly improves the application in the biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition to conductivity, these polymers display also antibacterial activity [6][7][8][9][10]. Five organic dyes differing in molecular structure have been selected for the present study (Figure 2) for their antibacterial effect reported in the literature: crystal violet (triphenylmethane dye) [14][15][16][17], neutral red (phenazine dye) [18,19], methyl orange (azo dye) [20], acriflavine (acridine dye) [21][22][23], and methylene blue (thiazine dye) [18,22,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to conductivity, these polymers display also antibacterial activity [6][7][8][9][10]. Five organic dyes differing in molecular structure have been selected for the present study (Figure 2) for their antibacterial effect reported in the literature: crystal violet (triphenylmethane dye) [14][15][16][17], neutral red (phenazine dye) [18,19], methyl orange (azo dye) [20], acriflavine (acridine dye) [21][22][23], and methylene blue (thiazine dye) [18,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial activity has also been demonstrated in systems including conducting polymers, such as polyaniline [25][26][27] and polypyrrole [7][8][9]20,23,28]. In this case, however, such activity may also be caused by residual reactants, low-molecular-weight by-products, polypyrrole counter-ions (Figure 1), and any potential additives.…”
Section: Introductionmentioning
confidence: 99%